DAMPAK COVID-19 TERHADAP STRUKTUR MODAL, LEVERAGE, PROFITABILITAS DAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR INDUSTRI DASAR DAN KIMIA PADA BEI - Angelia Christina Putri Prasetyo; Widhian Hardiyanti (Jurnal Akuntansi dan Pajak, 2023)
The COVID-19 pandemic has spread to all corners of the world and affected all aspects of life. The biggest impact come from the economic sector, formed in lockdown system and PPKM (Pemberlakuan Pembatasan Kegiatan Masyarakat), where those systems limit community / citizen to carry out work and daily activities. As a result, there is significant decrease in people's income and purchasing power for goods and services. Therefore, the purpose of this study is to find out whether or not COVID-19 has an impact on Capital Structure, Leverage, Profitability and Firm Value, where the decrease of people's purchasing power for goods and services significantly affected the companies financial condition. The study uses quantitative research methods where the data is taken from financial statements of companies listed on the Indonesia Stock Exchange. The study uses purposive sampling where the result samples are 140. From this research, the writer found out that there were no significant differences in Capital Structure, Profitability and Firm Value. However, there were significant differences between before and after Covid-19 for Leverage, so it can be concluded that COVID-19 only had impact on company Leverage, in economic sector.